Effect of phosphorus supplementation on weight gain and waist circumference of overweight/obese adults - Bassil, MS (2015)
Background: Phosphorus status is inversely correlated with body weight; however, the effect of phosphorus supplementation on body weight in a controlled design has not been studied. Methods: This is a double-blind, randomized, placebo-controlled trial of 63 adults aged 18–45 years with a body mass index (BMI) of greater than or equal to25 kg m−2 and normal kidney function at the American University of Beirut. Participants were randomly assigned to the placebo or phosphorus group where daily placebo or phosphorus supplements were ingested with three main meals (breakfast, lunch and dinner) for a period of 12 weeks. Primary outcomes were changes in anthropometric measures, blood metabolites (including lipid profile, glucose and insulin) and subjective appetite scores. The trial is registered with Clinical Trial.gov, NCT02329990. Results: Body weight was significantly lower in the phosphorus group when compared with the placebo group (−0.65 kg (95% confidence interval (CI) −1.69 to 0.40) vs 1.13 kg (95% CI 0.19 to 2.06), P=0.01). Similarly, BMI and waist circumference were significantly lower in the phosphorus group when compared with the placebo group (−0.24 kg m−2 (95% CI −0.59 to 0.12) vs 0.42 kg m−2 (95% CI 0.05 to 0.78), P=0.01; −3.62 cm (95% CI−4.90 to −2.33) vs 0.38 cm ( 95% CI−0.44 to 1.20), P<0.001; respectively). Several parameters of subjective appetite scores were decreased in the phosphorus-supplemented group. Conclusions: Phosphorus supplementation for 12 weeks significantly decreases body weight, BMI, waist circumference and subjective appetite scores. These findings support a promising role of the mineral phosphorus in the prevention and management of obesity, especially abdominal adiposity. The exact mechanisms of action and longer-term effects still need to be elucidated.